2006
DOI: 10.1088/0954-3899/34/2/007
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical treatment of fission fragment angular distribution

Abstract: A dynamical approach to the treatment of fission fragment angular distribution is developed. The approach is based on three-dimensional Langevin dynamics for shape collective coordinates joined with the Monte Carlo algorithm for the degree of freedom associated with the projection K of the total angular momentum of the fissioning system on the symmetry axis. The relaxation time of the tilting mode τ K is estimated. From fits to experimental data on the fission fragment angular distribution of heavy fissioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…The compound nuclei formed in such reactions have a temperature of about 1 MeV and low angular momenta. It has been found that the standard saddle-point transition-state model frequently predicted low values of the angular distribution anisotropy for reactions with more massive ions of carbon, oxygen, and heavier ions [14,15], and the experimental data are closer to the values obtained according to the scission-point transition-state model.…”
Section: Introductionsupporting
confidence: 52%
“…The compound nuclei formed in such reactions have a temperature of about 1 MeV and low angular momenta. It has been found that the standard saddle-point transition-state model frequently predicted low values of the angular distribution anisotropy for reactions with more massive ions of carbon, oxygen, and heavier ions [14,15], and the experimental data are closer to the values obtained according to the scission-point transition-state model.…”
Section: Introductionsupporting
confidence: 52%
“…An explicit expression for the friction tensor is given in Refs. [21,23,42]. The value k s = 1.0 corresponds to the standard "wall" and "wall-pluswindow" formulas [36,37,43], whereas values 0.2 < k s < 0.5 allow the reproduction of different features of the massenergy distribution, particle multiplicities in multidimensional Langevin calculations [5,6,11,24,25,42,44], and the widths of isoscalar giant resonances over a broad range of nuclear masses [38].…”
Section: Modelmentioning
confidence: 99%
“…[19]. Such description is more consistent than the application of the Metropolis algorithm [20,21,49]. The Langevin equation for the K coordinate allows the modeling of the relaxation process of K states depending on the instantaneous physical properties of fissioning system such as temperature and moment of inertia instead of treating the corresponding relaxation time τ K as a free parameter [20][21][22].…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we also use the three-dimensional Langevin model was developed in references (Karpov et al, 2001(Karpov et al, , 2007Nadtochy et al, 2002;Ryabov et al, 2008) to reproduce experimental data on the average pre-fission proton and alpha multiplicities for 227 Pa. The dynamical model has been described in detail in our previous papers (Eslamizadeh, 2011b(Eslamizadeh, , 2012b(Eslamizadeh, , 2013.…”
Section: Description Of the Model And Basic Equationsmentioning
confidence: 99%